Biophysical Interactions in Fragmented Marine Canopies: Fundamental Processes, Consequences, and Upscaling - Folkard, Andrew M. (Frontiers in Marine Science, 2019)
Spatial fragmentation is a near-ubiquitous characteristic of marine canopies. Biophysical interactions with fragmented canopies are multi-faceted and have many significant implications at multiple scales. The aims of this paper are to review research on biophysical interactions in fragmented marine canopies, identify current gaps in knowledge and understanding, and propose ways forward. The review starts at the patch/gap scale and focuses initially on hydrodynamic interactions. It then considers the consequences of these interactions for particulate and dissolved material, and distributions of canopy-associated organisms. Finally, it addresses issues of upscaling to landscape-scale and ways in which this research can be applied to marine landscape management. Work on a broad range of canopy types is considered, including micro-algal biofilms and turf algae; macro-algae, seagrasses and coral reefs; saltmarsh vegetation and mangroves. Although the focus is on marine canopies, insights from studies of fragmented canopies in other contexts are drawn on where relevant. These include freshwater environments and terrestrial forests, grasslands, crop canopies, and urban areas. Specific areas requiring greater attention are highlighted. As a result of this meta-analysis, the following recommendations are made for further research. A lack of basic data is identified across all canopy types regarding the formation, fate and spatial and temporal characteristics of canopy patches, gaps, and spatial structure. Studies of hydrodynamics with fragmented canopies would benefit from shifting focus toward more non-uniform, realistic configurations, while ecological research in this area would benefit from a move toward configurations that are more controlled and tractable for quantitative modeling. More comparative studies across canopy types would enable understanding of their biophysical interactions and their consequences to be more fully tested and developed. A greater incorporation of chemical aspects of canopy systems into work that has hitherto focused on biophysical interactions would also be pertinent. Upscaling of patch and gap-scale phenomena to landscape-scale is identified as a crucial topic, since it is at the latter scale that management efforts are most readily carried out. Overall, an approach that balances hydrodynamics, marine canopy ecology, spatial analysis of landscapes, biogeochemistry, and socio-environmental interactions is recommended.